2014
DOI: 10.3349/ymj.2014.55.1.178
|View full text |Cite
|
Sign up to set email alerts
|

Gradual Lengthening of the Ulna in Patients with Multiple Hereditary Exostoses with a Dislocated Radial Head

Abstract: PurposeMultiple hereditary exostoses of the forearm typically form in the distal ulna, causing disturbances in the growth of the ulna and functional disability. Multiple hereditary exostoses inhibit the growth of the ulna, leading to an acquisition of a varus deformity in the radius, which sometimes leads to dislocation of the radial head, the development of limitations in the pronation-supination of the forearm, and cosmetic problems.Materials and MethodsWe retrospectively reviewed the cases of four patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 18 publications
0
24
0
Order By: Relevance
“…Ham et al also suggested delaying the lengthening until after the age of 13-15 years [12]. Other studies reported satisfactory results after ulnar lengthening, but the mean follow-up times of their patients were short (< 2.5 years) [3,4] or the age at intervention was older than 10 years [5]. With a mean follow-up time of 4.2 years, the analysis of the radiographic parameters in this study shows initial improvement and then deterioration at last follow-up, however, the ulnar shortening and forearm pronation improved signi cantly by ulnar lengthening, and the cosmetic appearance improved signi cantly with the change of carrying angle (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ham et al also suggested delaying the lengthening until after the age of 13-15 years [12]. Other studies reported satisfactory results after ulnar lengthening, but the mean follow-up times of their patients were short (< 2.5 years) [3,4] or the age at intervention was older than 10 years [5]. With a mean follow-up time of 4.2 years, the analysis of the radiographic parameters in this study shows initial improvement and then deterioration at last follow-up, however, the ulnar shortening and forearm pronation improved signi cantly by ulnar lengthening, and the cosmetic appearance improved signi cantly with the change of carrying angle (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…[1,2]. Gradual ulnar lengthening has been widely used with successful reported results in managing forearm deformity [3][4][5][6][7]. However, the treatment remains controversial.…”
mentioning
confidence: 99%
“…A few articles deal with forearm deformities, including the deformities of the forearm in this genetic disease of multiple hereditary [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…In adults with radial longitudinal deficiency, factors such as grip strength, forearm length, and digital motion are more important for the individual's activity than radial angulation at the wrist 54 . In patients with multiple hereditary exostoses and a dislocated radial head, comprehensive treatment including excision of the forearm osteochondromas and gradual lengthening of the ulna improved clinical and radiographic parameters 55 .…”
Section: Pediatric and Adult Reconstructionmentioning
confidence: 99%